Islam Supports Democracy:The Views of Partai Islam Se-Malaysia (PAS) and Their Implementation in the Recruitment of the Party’s Members and Leaders - Ahmad Ali Nurdin (P3M STAIN Kudus, 2019)
This paper discusses the views of Partai Islam Se-Malaysia (PAS) on democracy and its implementation in real politics in Malaysian context. I analyze PAS views on the relationship between Islam and democracy, their style in recruiting members and leaders of the party to demonstrate that this Islamic political party follows democratic rules. PAS believes that democracy and Islamic values are compatible and it is a good political tool for an Islamic party like PAS to reach its political goals.  By examining the process of recruitment of members and leaders of PAS as the cases, the paper shows that commitment of PAS in toning up democracy in Malaysia could be viewed in their style of recruiting their leaders. The PAS has exercised democratic rules in their internal party activities, particularly in the way they recruit their members and how they chose their leaders.